Autoestima y estrés académico en estudiantes del quinto nivel de educación inicial Facultad de Ciencias de la Educación y Humanidades, Iquitos 2022 - Aspajo Arevalo, Martha Elizabeth (2024)
The general objective of the study is to relate self-esteem with academic stress in students of the fifth level of the professional career of initial education, the type of non experimental research, with descriptive correlational design of the transversal type, with a population of 135 students and a sample of 94 students of the professional career of initial education of the Faculty of Education. The relationship between self-esteem and academic stress in students of the fifth level of the professional career of initial education, a Pearson correlation coefficient rxy= - 0.753 is observed, this indicates a high, inverse and negative relationship between these variables, which is observed in the scatter diagram in which the points suggest a linear trend of negative slope, that is, inversely proportional jointly, this means that while self-esteem increases, academic stress in the students of initial education decreases notably. The study concludes that according to Student's t-statistic value = - 12.2354; p-value (bilateral significance) = 0.000, this value is less than 0.05, therefore we reject the Ho (null hypothesis) and accept the Ha (alternative hypothesis), concluding that self esteem and academic stress are significantly related.